Outcomes of Patients with and without Nighttime Awakening Symptoms After Carpal Tunnel Release. (January 2022) - Lander, Sarah; Lander, Alex; Hammert, Warren C.
Background: A common symptom associated with carpal tunnel syndrome (CTS) is nighttime awakening (NTA), which typically resolves quickly following carpal tunnel release (CTR). The early improvement in those who do not wake-up at night is less clear. This study investigates outcomes following CTR in patients with preoperative NTA symptoms compared to those without at 6 weeks and 3 months.Methods: Patients diagnosed with CTS who proceeded with CTR and agreed to participate in a prospective study completed the Boston Carpal Tunnel Questionnaire (BCTQ) and Michigan Hand Outcome Questionnaire (MHQ) at their preoperative appointment and 6-week and 3-month follow-ups. We compared outcomes between time points for improvement.Results: Of 45 patients, 37 patients with NTA had BCTQ scores of 3.09, 1.86, and 1.50 at preoperative, 6-week, and 3-month follow-up, respectively, and MHQ scores of 56.68, 74.91, and 81.01. NTA patients had improvement of both BCTQ and MHQ at 6 weeks and 3 months. Nonawakening patients had BCTQ scores of 2.58, 2.15, and 1.86 and MHQ scores of 57.94, 62.71, and 72.16, respectively. This cohort did not have significant improvement of MHQ at 6 weeks, but did at 3 months. The BCTQ severity scores in the nonawakening patients had significant improvement at both 6 weeks and 3 months, but did not at either time point for the BCTQ functionality scores. At 6 weeks, 2/37 patients continued to have NTA and no patients had NTA at 3 months.Conclusion: Patients with CTS and NTA symptoms had significant improvements in BCTQ and MHQ at 6 weeks and 3 months. Patients who did not awaken at night did not have significant improvements when evaluating BCTQ functional results, although they did improve when analyzing for BCTQ for symptom severity and MHQ, but not to the same level as those that do awaken and improvement was slower based on MHQ scores.